Amr̥taśārdā : Mahārāshṭra Sāhitya Parishada, Puṇe, 1906-1981, amr̥ta mahotsava smaraṇikā - Behere, Gaṇapatī Vāsudeva (Maharāshṭra Sāhitya Parishada, 1981)
Souvenir to commemorate the completion of 75 years by the Maharashtra Sahitya Parishad; comprises vignettes of Marathi litterateurs.